2019
DOI: 10.3390/rs11242919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Five Satellite Top-of-Atmosphere Albedo Products over Land

Abstract: Five satellite top-of-atmosphere (TOA) albedo products over land were evaluated in this study including global products from the Advanced Very High Resolution Radiometer (AVHRR) (TAL-AVHRR), Moderate Resolution Imaging Spectroradiometer (MODIS) (TAL-MODIS), and Clouds and the Earth's Radiant Energy System (CERES); one regional product from the Climate Monitoring Satellite Application Facility (CM SAF); and one harmonized product termed Diagnosing Earth's Energy Pathways in the Climate system (DEEP-C). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To fully understand the performance of the five TOA OLR products in different regions, we divided the world area into 12 parts (2 additional ANT and GRL parts added to [18]). Then, similar to Figure 4, we also calculated the HIRS, CERES, GEWEX, AVHRR, and CLARA monthly mean TOA OLR anomalies in each region, as shown in Figure 5.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To fully understand the performance of the five TOA OLR products in different regions, we divided the world area into 12 parts (2 additional ANT and GRL parts added to [18]). Then, similar to Figure 4, we also calculated the HIRS, CERES, GEWEX, AVHRR, and CLARA monthly mean TOA OLR anomalies in each region, as shown in Figure 5.…”
Section: Results Analysismentioning
confidence: 99%
“…Zhan et al (2019) intercompared five satellite TOA albedo products over land and found that the differences among these products in the high-latitude regions were relatively larger, which is different from the results of Zhan et al (2018). Larger differences were also found during the years before 2000 [18]. Susskind et al (2012) examined spatial anomaly time series of OLR as determined using observations from CERES and AIRS and found excellent agreement of the two OLR datasets in almost every detail [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the inundation of literature, formal and informal, by plots of time-series of the global temperature, a literature review showed that there is little information on the climatic information of the Earth's albedo in absolute terms. A few papers and web sites give some "anomalies" on the monthly scale; for example, the site Measuring Earth's Albedo by NASA [126] shows a graph with annual "anomalies" for the period 2000-2011; this is also the case with a recent publication by Zhan et al [127]. One of the rare exceptions is a publication by Loeb and Wielicki [128], which gives a time-series plot of the top of atmosphere (TOA) global albedo but, unfortunately, only for one year, 2010.…”
Section: Conflicts Of Interestmentioning
confidence: 92%